Reformed GST: Challenges and Opportunities (PANEL DISCUSSION-II) (The Pakistan Development Review, 2010)
Firstly I would like to appreciate the views and compliments. I was mentioning to Mr Idrees Khawaja that perhaps they could have chosen a much better representative for the private sector because my view is distinctly in the minority in case of RGST. I will just share with you where the private sector stands on the issue of RGST, what their opinion is and then I will give you my own stance on the subject as well as justification on the same. As you would know from newspapers and other media, the private sector is strongly against the imposition of RGST. The vast majority of chambers, which represent the bulk of Pakistan’s private sector, have been vociferous in the opposition of RGST. I must mention here that in addition to my responsibilities at Engro, I also serve in the role of Chairman of Pakistan Business Council, which was created a few years ago. Pakistan Business Council comprises of largest business groups of Pakistan. Every single large business group of Pakistan is its member, including some of the key multinationals operating in Pakistan. Pakistan Business Council formally supported the RGST, even during its hearing in the National Assembly Finance Committee. Part of the difference that you see here can be explained in terms which would be flattering to us. We have been part of the industry since a very long time but we realise where the world is headed, and understand that a modern country cannot progress and cannot be run effectively with a tax-to-GDP ratio which is in single digit. But since the private sector is not significantly represented here, I think it is only fair that I try to bring forth where some of their apprehensions come from. We at large businesses have management systems and teams who are sophisticated enough to deal with complex systems. We have the necessary resources which enable us to engage the most expensive lawyers in Pakistan, and fight with the FBR when we see corruption or unfair practices being carried out. We can also raise issues that we face in front of the highest authority in the country. The vast majority of the Pakistani businessmen are small traders or small manufacturers. They do not have the systems and resources like large companies. Moreover, fact of the matter is that the tax machinery in Pakistan is both incompetent and corrupt. Therefore, it is a very legitimate concern on part of the business community that the RGST will make their lives difficult, more than the way economic theory portrays it to be. This is because there are certain realities that have to be looked at.